BIODEGRADATION OF PHENOLIC EFFLUENTS USING UPFLOW PACKED BED REACTORS - T. , Murugesan (2007)
The biological methods for the treatment of phenolic effluents in continuous reactors using immobilized microorganisms have gained wide recognition due to their high degradation efficiency and their usage at high dilution rates. The present study in a cocurrent upflow packed bed reactor involves the treatment of phenolic effluents obtained from petrochemical industries, using a microorganism Pseudomonas putida (NCIM 2174), immobilized on alginate beads. A quantitative analysis of the effect of mass transfer coefficients on the operating parameters namely, flow rate, particle diameter, and initial concentration of phenols, etc. is carried out for the biodegradation of phenols in an upflow packed bed reactor. From the mass transfer coefficients, the overall reaction rate was found to be first order with the mass transfer as the rate-limiting step. A mass transfer model of the form jD = K(Re)n−1 was developed. The values of ‘K’ and ‘n’ were found to 1.45 and 0.725 respectively for the petrochemical effluents treated with P. putida on alginate beads.